Performance Of Indigenous Rituals And Forest Ecosystem Sustainability: An Ethnographic Study Of Local Communities - Wijaya Wijaya; Ayesha Begum; Sylvia Nabuuma (Journal of Humanities Research Sustainability, 2025)
Background. Indigenous rituals have long played a vital role in shaping human–nature relationships, often embedding ecological knowledge within cultural practices. In many forest-dependent communities, these rituals function not only as spiritual expressions but also as informal governance systems regulating resource use, biodiversity conservation, and environmental stewardship. The growing pressures of modernization, land-use change, and climate variability raise concerns about the continuity of such traditions and their ecological implications. Purpose. This study aims to examine the performance of indigenous rituals and their contribution to forest ecosystem sustainability within local communities. Method. An ethnographic research design was employed, involving participant observation, in-depth interviews with ritual practitioners and community elders, and analysis of ritual artifacts and narratives. Fieldwork was conducted over six months in two forest-dependent communities known for their active ritual traditions. Results. Findings reveal that rituals act as socio-cultural mechanisms for enforcing sustainable harvesting norms, protecting sacred groves, and transmitting ecological values intergenerationally. However, external economic pressures and declining youth participation threaten their efficacy. Conclusion. The study concludes that integrating indigenous ritual knowledge into formal conservation policies can strengthen forest governance and cultural resilience. Recognition and empowerment of such practices are essential for holistic and culturally grounded ecosystem management strategies.